Therapeutic effects of Bombax ceiba flower aqueous extracts against loperamide-induced constipation in mice - Liuping Wang; Shiyuan Xie; Xuan Jiang; Caini Xu; Youqiong Wang; Jianfang Feng; Bin Yang (Taylor & Francis Group, 2023)
AbstractContext Bombax ceiba Linnaeus (Bombacaceae) is known as silk cotton tree, the flowers of which are used in many medicinal applications.Objective To investigate the therapeutic effect of B. ceiba flower aqueous extracts (BCE) against loperamide-induced constipation and characterize the chemical composition of BCE.Materials and methods Sixty male Kunming mice were divided into control (saline), model (10 mg/kg loperamide + saline), phenolphthalein (10 mg/kg loperamide + 10 mg/kg phenolphthalein) and different dosage of BCE (10 mg/kg loperamide + 40, 80 and 160 mg/kg BCE, respectively) groups, and received intragastric administrations for eight days. Faecal water content, number of faeces, first black-stool defecation time and gastrointestinal transit rates were evaluated. Various biochemical and molecular biomarkers were assessed in blood and colon. UPLC-ESI-QTOF-MS/MS was used to tentatively identify the composition of the BCE.Results BCE treatment (160 mg/kg) could increase faecal water (15.75%), faeces number (11.65%), gastrointestinal transit rate (25.37%) and decrease first black-stool defecation time (24.04%). The BCE (80 mg/kg) increased the serum level of motilin (30.62%), gastrin (54.46%) and substance P (18.99%), and decreased somatostatin (19.47%). Additionally, the BCE (160 mg/kg) reduced the mucosal damage, restored colonic goblet cell function, down-regulated the protein expression of AQP3 (33.60%) and increased c-kit protein expression (11.63%). Twelve known compounds, including protocatechuic acid, chlorogenic acid and rutin, previously reported in B. ceiba, were identified in the BCE.Discussion and conclusions This study suggested that BCE is a promising agent for the treatment of constipation.